Mystery shopping jako metoda badania standardów obsługi klienta - Gregor, Bogdan; Grzegorczyk, Małgorzata (Mystery Shopping as a Method of Research of Customer Service Standards, 2006)
Mystery shopping is a market research method which allows to improve quality of customer service, estimate training needs and budget necessary for development of employees. One can observe increasing usage of this method in business practice but in academic literature there is still a lack of definition and description of mystery shopping methodology. This method is usually described superficially together with other kinds of marketing observations. The aim of this paper is to present the methodology of mystery shopping and try to digest the knowledge in reference to marketing research theory.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 585-591